Portuguese Public Debt Management During The European Sovereign Debt Crisis - a case study - Lourenço, Catarina De Miranda De Matos (2020)
The presentcase study analyses the Portuguese publicdebt management during theEuropeanSovereign debtcrisis, namely the decisions undertook by the Government and by the Portuguese Debt Management Agency.On April 6th,2011, Portugal requestedofficial financial assistance, beginning a three-year period in which market access was severely constrained.This case studyfocus onthe behaviourof relevant parameters,such as the evolution of yieldsand spreads for Government bonds, the shareof public debt held by domestic and non-domestic investors through time, the progressionof Portuguese debt ratings and thecomposition of the stock of public debt.